Trust, consistency and transparency: in-home respite needs and preferences of people living with dementia and their carers - Grogan, Caroline; Harriman, Sarah; Martin, Elizabeth; Waite, Rebecca; Fisher, Olivia (Frontiers in Health Services, 2025)
PurposeTo identify the needs, preferences, and perspectives of people living with dementia and their carers to inform design and implementation of an in-home respite service.Design/MethodologyExploratory, interpretivist, pre- implementation qualitative study using Consolidated Framework for Implementation Research.ParticipantsPeople living with dementia and carers.Data collectionMulti-person and individual semi-structured interviews.Findings15 participants: Four people living with dementia, 11 carers. Carers are exhausted and want a say in the development and delivery of services. People living with dementia and carers need safety, trust in respite staff and in the organisation, consistency, additional supports, and clear, transparent communication.Future directionsFindings will inform in-home dementia respite models of care, better supporting family carers and people living with dementia to age-in-place. Recommendations: provide an orientation session; clear, transparent communication; provide/refer carers to wrap-around supports; ensure consistency including having consistent carers, arrival times, services provided and routines; emergency and scheduled options.